Abnormal Intrinsic Functional Interactions Within Pain Network in Cervical Discogenic Pain - Zhang, Hong; Xia, Dongqin; Wu, Xiaoping; Liu, Run; Liu, Hongsheng; Yang, Xiangchun; Yin, Xiaohui; Chen, Song; Ma, Mingyue (Frontiers in Neuroscience, 2021)
Cervical discogenic pain (CDP) is mainly induced by cervical disc degeneration. However, how CDP modulates the functional interactions within pain network remains unclear. In the current study, we studied the changed resting-state functional connectivities of pain network with 40 CDP patients and 40 age-, gender-matched healthy controls. We first defined the pain network with the seeds of posterior insula (PI). Then, whole brain and seed-to-target functional connectivity analyses were performed to identify the differences in functional connectivity between CDP and healthy controls. Finally, correlation analyses were applied to reveal the associations between functional connectivities and clinical measures. Whole brain functional connectivity analyses of PI identified increased functional connectivity between PI and thalamus (THA) and decreased functional connectivity between PI and middle cingulate cortex (MCC) in CDP patients. Functional connectivity analyses within pain network further revealed increased functional connectivities between bilateral PI and bilateral THA, and decreased functional connectivities between left PI and MCC, between left postcentral gyrus (PoCG) and MCC in CDP patients. Moreover, we found that the functional connectivities between right PI and left THA, between left PoCG and MCC were negatively and positively correlated with visual analog scale, respectively. Our findings provide the direct evidence for how CDP modulates the pain network, which may facilitate understanding the neural basis of CDP.